Investigation of Bi0.5(Na0.80K0.20)0.5TiO3-LiNbO3-Ba(Ti0.90Sn0.10)O3 Lead-Free Piezoelectric Ceramics. Issue 1 (12th February 2021) - Wannasut, Pimpilai; Jaita, Pharatree; Khamman, Orawan; Jaiban, Panupong; Jiansirisomboon, Sukanda; Watcharapasorn, Anucha
Abstract: The ceramics with the formula of (1- y )[0.995Bi0.5 (Na0.80 K0.20 )0.5 TiO3 -0.005LiNbO3 ]- y Ba(Ti0.90 Sn0.10 )O3 or (1- y )[0.995BNKT-0.005LN]- y BTS ( y  = 0-0.05 mol fraction) were successfully prepared by a conventional mixed oxide method. It was found that all compositions showed single phase with a mixed rhombohedral/tetragonal structure. The highest piezoelectric coefficient ( d33 = 175 pC/N) with good dielectric ( εr = 1775, tanδ  = 0.0534) and ferroelectric properties ( Pr = 12.33 µC/cm 2, Rsq = 1.37) was obtained for y  = 0.04 sample. The bipolar S-E loops showed highest Smax = 0.25% at y  = 0.05.